KAJIAN LAJU OKSIDASI MINERAL SULFIDA PADA BATUAN PENGAPIT LAPISAN BATUBARA - Setia Wahyudi, Herry
Inclining of rate of the acid mine drainage (AMD) is mostly influenced by coal mining activities because of overburden excavation which contain of oxidized sulfide minerals. In this term, the mining company had to study carefully for reaching out the minerals contents as well based on government regulation that related to environmental issues. The study should be figured out from geochemical approach as well as the AMD rate (known as pyrite). Experimentation in laboratory scale was conducted by using four sample which was taken from overburden field. Some mineralogy, static and kinetic testing were applied on the samples number of ABC 01, ABC 02, ABC 03 and ABC 04. Geochemical characterization of rock was made based on static test data (NAG pH, MPA, ANC, NAPP) which were confirmed by kinetic test results (pH and TDS of leachate water). Pyrite oxidation rate was calculated based on moles of total iron and sulfate in leachate. Pyrite oxidation rate based on moles of total iron and sulfate will be verified by pyrite oxidation rate based on geochemical modeling by PHREEQCl which conduct based on mineralogy test data and ion/element of leachate. Static and kinetic test results showed that the ABC 01 and ABC 03 samples were included as potentially acid forming (PAF), while ABC 02 and ABC 04 samples were classified as non-acid forming (NAF). Pyrite oxidation rate based mol of sulphate in leachate is identical to pyrite oxidation rate based on geochemical modeling of PHREEQCl, while the pyrite oxidation rate based on mol of total iron is lower than the other two approaches. Leachate Eh-pH plotting indicate that iron tends to presipitated in leachate. Ion analysis in leachate shows that the ratio of sulfate and alkali tends to be close to equilibrium so pyrite oxidation rate based on moles of sulphate is more reliable to apply.